Why Do People Buy Insurance? A Modern Answer to an Old Question - Markus Fels (ZBW - Leibniz Information Centre for Economics, 2021)
I revisit the question of which motive underlies insurance demand. I draw on the literature of state-dependent utility and on the literature of imperfectly divisible consumption to argue that the general purpose of insurance is not a risk transfer, but meeting a conditional need. In this way, insurance aligns the risk in one's ftnancial endowment with the risk in one's ftnancial needs. This generalization extends the classical view of insurance. I show how this extension greatly simpliftes the generalization of classic results. I also discuss how the novel deftnition has implications for our discipline's research agenda and policy advice
Keywords: D01; D81; G22; 330; Insurance; Risk Aversion; State Dependence; Divisibility of Consumption; Risk Preferences